Trombocitemia essencial. Terapêutica com alfa interferão. - L Lebre; A Sousa; J Sampaio; L Novais; E Júnior; R Coelho; J Simões (Acta Médica Portuguesa, 1991)
A clinical case of essential thrombocythaemia is presented to demonstrate good therapeutic response to subcutaneous Alpha-2b Interferon in a dosage of 3 x 10(6) units, three times a week. Based on this case and on a literature research we propose that Alpha-2b Interferon is a legitimate alternative to alkylating agents or radioactive phosphorus (32P), showing identical efficacy and less Leukemogen effect.